The Impact of Intellectual Capital On Firm Performance: An Application of VAIC Model - Baiq Luluk Hariatun; Robith Hudaya (Business Management, 2025)
This study aims to analyze the impact of intellectual capital (IC) on firm performance as measured by Tobin's Q. In this study, intellectual capital is measured using the Value Added Intellectual Coefficient (VAIC) method which consists of three components, namely Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA). This study implements a quantitative method with panel data and is analyzed using the Random Effect model. The results show that VACA has a positive and significant influence on firm performance, while VAHU does not show a positive influence, and STVA shows a positive although insignificant influence. The findings suggest that the efficient use of physical and financial capital plays a crucial role in increasing the market value of the firm, while the role of human capital and structural capital still needs to be optimized. This study indicates that proper management of intellectual capital can be an important strategy to build sustainable competitive advantage.